Identification of a glutamine metabolism reprogramming signature for predicting prognosis, immunotherapy efficacy, and drug candidates in bladder cancer - Xu, Yan; Xia, Zhixiu; Sun, Xiaoyu; Wei, Baojun; Fu, Yang; Shi, Du; Zhu, Yuyan (Frontiers in Immunology, 2023)
Background: Bladder cancer (BC) is the most common malignancy of the urinary system. However, patient prognosis and treatment outcomes in bladder cancer are difficult to predict because of high tumor heterogeneity. Since abnormal glutamine metabolism has been considered a key factor driving the progression of bladder cancer, it is necessary to assess the prognosis and therapy efficacy of bladder cancer based on glutamine metabolism-related genes. Methods: We used bladder cancer sample data downloaded from The Cancer Genome Atlas to identify glutamine metabolism-related genes as prognostic predictors, and established a novel glutamine metabolism immunity index (GMII) using univariate and multivariate COX regression. Based on GMII, bladder cancer patients were divided into high-risk and low-risk groups, and systematic analysis was conducted for clinical features, somatic mutation, immune cell infiltration, chemotherapy response, and immunotherapy efficacy. The potential small-molecule drugs for the GMII core target proteins had been identified with molecular docking. Results: GMII consisting of eight independent prognostic gene factors was an excellent predictor of survival in patients with bladder cancer and had been validated using multiple datasets. Compared with the high-risk group, the low-risk group had significantly better responses to gemcitabine, and immune checkpoint blockades. In addition, we predicted 12 potential small-molecule drugs that could bind to the three GMII core target proteins. Conclusions: GMII could accurately predict the prognosis, immunotherapy response, and candidate small-molecule drugs in BC patients. Furthermore, the novel “Glutamine Metabolism-related Genes”-guided strategy for predicting the survival and chemo-immunotherapy efficacy might be also applied to more cancers other than BC.